INTERNALIZATION MODEL OF SOFT SKILL OF STATE DEFENSE FOR STUDENTS OF FACULTY OF SOCIAL AND POLITICAL SCIENCES THROUGH INTEGRATIVE AND SUSTAINABLE ACTIVITIES - Machya Astuti Dewi; Asep Saepudin; Muharjono Muharjono; Indro Herry Mulyanto; Kurnia Arofah (Jurnal Pertahanan & Bela Negara, 2019)
This article is the result of institutional research, which aims to develop a model of internalization of state defense soft skills for FISIP students of UPN "Veteran" Yogyakarta who can graduate with state defense character. In this article, several stages were carried out, namely, the first stage in formulating the state defense soft skills derived from the basic values of state defense. The next stage is to arrange the forms of activities carried out starting to be accepted as new students until students being graduated. The activities consist of curricular, co-curricular and extra-curricular activities. The final stage is to arrange the stages of internalization of state defense soft skills based on the forms of the activities. The internalization stage begins with the stages of introduction, awareness, reinforcement, actualization and further strengthening. This third stage is a model of internalization of integrated and sustainable state defense soft skills.Keywords: internalization, soft skills, state defense, integrated, sustainable